Antimicrobial Activities of Two Scorzonera Species Growing in Turkey - SARI, AYNUR; OZBEK, BERNA; OZGOKCE, FEVZi (Asian Journal of Chemistry, 2010)
The antimicrobial activities of the ethanolic extracts and petroleum ether, ethyl acetate and n-butanol fractions obtained from the subaerial parts of two Scorzonera species (S. latifolia and S. veratrifolia) (Asteraceae) have been tested against Staphylococcus aureus ATCC 6538, Staphylococcus epidermidis ATCC 12228, Escherichia coli ATCC 8739, Klebsiella pneumoniae ATCC 4352, Proteus mirabilis ATCC 14153, Pseudomonas aeruginosa ATCC 1539, Salmonella typhi, Shigella flexneri and Candida albicans ATCC 10231 using microbroth dilution technique. The ethyl acetate fractions of both S. latifolia and S. veratrifolia showed the highest antimicrobial activity against Staphylococcus aureus (MIC values 19.52 and 39.06 μg/mL, respectively).